Analisis Implementasi Akuntansi Lingkungan dalam Mewujudkan Keberlanjutan Bisnis pada BUMDes Berdikari Abadi Sedatigede Sidoarjo - Lola Via Marcellina; Muhammad Taufiq Hidayat (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study analyzes the implementation of green accounting and its contribution to business sustainability in "Berdikari Abadi" BUMDes in Sedatigede Village, Sidoarjo. The research focuses on the 3R Waste Processing Site (TPS 3R) business unit, established to address waste problems. A qualitative case study approach was employed, with data collected through interviews, observation, and documentation. The findings indicate that green accounting practices have not been optimally implemented. Costs related to environmental activities, such as transportation and maintenance, are still recorded as part of general operational costs without specific classification and reporting. Nevertheless, the TPS 3R unit has made real contributions to sustainability across economic (income from recycling), social (increased community participation), and environmental (reduced waste volume) aspects. The main obstacles include limited human resource capacity and the lack of a supporting accounting system. This study recommends separating environmental cost accounts, preparing simple sustainability reports, and enhancing managerial capacity. Theoretically, this study enriches the literature on adapting green accounting at the village level. Practically, the findings can guide BUMDes and village governments in developing accountable and sustainable business governance.